Risk Mitigation Strategy in Financing Without Collateral at PT. BPRS Sarana Prima Mandiri Pamekasan - Iqbal Rafiqi; Ulum, Miftahul; Hidayat, Moh. Helmi; Jufri, Achmad (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2023)
Financing without collateral BPRS SPM Pamekasan is proliferating. Every year there is always an increase in customers by 75% from an average of 35%. The problem raised in this research is how to implement collateral-free financing and risk mitigation. This research is descriptive qualitative research with a case study model. Data collection techniques use observation, interviews, and documentation related to risk mitigation of collateral-free financing at BPRS Sarana Prima Mandiri Pamekasan. The results of this study indicate (1). PT. BPRS Sarana Prima Mandiri can provide financing for productive businesses. The customer's business funding needs are financed 100% by the BPRS SPM. The customer is the business manager, and the maximum period is six months. The payment procedure is carried out every day, while profit sharing is done once a month, which will be disbursed when the financing is said to be paid off. (2). The risk mitigation process carried out by BPRS Sarana Prima Mandiri Pamekasan is risk identification, namely looking at the character of the prospective customer, working capital capabilities, income that does not exceed the payment ability of the prospective customer, and education on customer product marketing.